Pregnancy and neonatal outcomes of ICSI using pentoxifylline to identify viable spermatozoa in patients with frozen-thawed testicular spermatozoa - Dong, Jing; Yin, Mingru; Wu, Ling; Wang, Tiantian; Li, Menghui; Zhang, Wei; Ma, Meng; Li, Bin (Frontiers in Endocrinology, 2024)
Introduction: Although the effectiveness of pentoxifylline (PF) as a selective inhibitor of phosphodiesterase to enhance sperm motility through increasing cyclic nucleotide in cases of absolute asthenozoospermia has been demonstrated for ICSI, data related to babies born from the PF-ICSI are still severely lacking. Concerns have been raised regarding the potential embryotoxicity of PF due to the controversial results obtained from the analysis of this compound on animal embryo development.This study aimed to determine whether the application of PF to trigger frozen-thawed TESA (testicular sperm aspiration) spermatozoa increases the risk of adverse obstetric and neonatal outcomes compared with non-PF frozen-thawed TESA ICSI and conventional ICSI using fresh ejaculation.A total of 5438 patients were analyzed in this study, including 240 patients underwent PF-TESA ICSI (ICSI using PF triggered frozen-thawed testicular spermatozoa), 101 patients underwent non-PF TESA ICSI (ICSI using frozen-thawed testicular spermatozoa) and 5097 patients underwent conventional ICSI using fresh ejaculation. Propensity score matching was executed to control the various characteristics of patients.Results: No significant differences in pregnancy outcomes were observed among the three groups (PF-TESA ICSI, non-PF TESA ICSI and conventional ICSI), including biochemical pregnancy, clinical pregnancy, implantation, miscarriage, ectopic pregnancy, multiple pregnancy, and live birth, following propensity score matching.Additionally, neonatal outcomes were found to be similar among the three groups, with no statistical differences observed in the birth defect, birth weight, gestational age, preterm birth, and early-neonatal death.Discussion and conclusion: PF-ICSI may be an alternative treatment in patients using frozen-thawed testicular spermatozoa, resulting in comparable pregnancy and neonatal outcomes.